Walking as embodied research
1 online resource (xiv, 373 pages)
Keywords: "This volume explores walking as a form of research practice. The contributions by a wide range of scholars and practitioners cover a variety of urban and non-urban landscapes around the world. They describe and reflect on ways of working that involve walking, and the kinds of ideas that inspire walking practices. A key theme is embodied research and how the act of walking brings the body into presence as a material part of the research process. The book also examines the ways in which walking opens out to multi-sensorial understandings and appreciations of landscape, and touches on ideas of presence and witnessing. Landscapes are themselves considered to be in motion, subject to the changing regimes of the era that we inhabit and the effects of Anthropogenic climate change. Finally, walking is thought about as political intervention and the volume addresses questions of social justice, decolonial futures and alternative forms of knowledge. It will serve as a source of inspiration to readers from across the humanities and social sciences who are interested in walking methodologies and in new and sustainable research practices"--